78 important questions every leader should ask and answer - Clarke-Epstein, Chris (New York : AMACOM, 2002)
Annotation Great leaders have many talents, but one critical skill -- often unrecognized -- is the ability to ask and answer questions. This unique book offers 78 questions that leaders at all levels need to ask and answer both inside and outside the organization. Leaders who master this question-response technique will gain much useful information about what is really going on in their businesses, as well as the admiration of employees, customers, and others with whom they interact. The questions and answers cover a range of common and uncommon situations, including: the need to connect employees' efforts to company goals; layoffs, business downturns, and mergers; personal crises of employees; coaching and mentoring sessions; and customer retention. The book even includes advice on answering questions when the answer is "I don't know" or "I can't tell you." With worksheets in each chapter, it prepares leaders to ask important questions of: Customers ("Why do you do business with our competition?") -- Employees ("What's a recent management decision you didn't understand?") -- And even themselves ("What do I want to be remembered for?")
Questions Leaders Need to Answer -- What do you see happening in our organization over the next twelve months? -- What is the future of our industry? -- What gets you excited about the future? -- How do you learn about our customers? -- How do you know what I do in my job? -- How can I advance in our organization? -- How do you make decisions? -- How do you make time to think? -- What makes you angry in the workplace? -- How do you measure success? -- How do you re-ignite your enthusiasm for your job? -- What do you love about your job? -- What do you do just for fun? -- What gives your life meaning? -- Answers for Special Situations -- During a Business Crisis -- What's happening? -- What's going to happen next? -- What's going to happen to me? -- Am I going to have a job next month? -- What's the long-term impact of this crisis? -- During a Merger or Acquisition -- What's going to change? What's going to happen to my job? -- Who will be my leader? -- Will our values last? -- During the Personal Crisis of an Employee -- What will the organization do to support me? What are my benefits? What will this mean for my career? -- Delivering Tough Answers -- Answering when the answer is I don't know -- Answering when the answer is No -- Answering when there isn't an answer -- Answering when you can't answer -- Answering when no one wants to hear the answer -- Answering a question that's just too personal -- Conclusion: Some Final Questions -- Appendix: Good Questions from Other Leaders.
Includes bibliographical references (pages 212-214) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Leadership; Communication in organizations; Corporate culture; Public relations; Leadership; Communication dans les organisations; Culture organisationnelle; Relations publiques; public relations; BUSINESS & ECONOMICS -- Leadership; Communication in organizations; Corporate culture; Leadership; Public relations